Status and Mating Success Amongst Visual Artists - Clegg, Helen; Miell, Dorothy; Nettle, Daniel (Frontiers in Psychology, 2011)
Geoffrey Miller has hypothesized that producing artwork functions as a mating display. Here we investigate the relationship between mating success and artistic success in a sample of 236 visual artists. Initially, we derived a measure of artistic success that covered a broad range of artistic behaviors and beliefs. As predicted by Miller’s evolutionary theory, more successful male artists had more sexual partners than less successful artists but this did not hold for female artists. Also, male artists with greater artistic success had a mating strategy based on longer term relationships. Overall the results provide partial support for the sexual selection hypothesis for the function of visual art.